Key trends in information security. (November 2015) - Maule-ffinch, Bradley
Abstract : If you cast your mind back 10 or 20 years, the word 'hack' did not carry half the threat and malice it does today. For many, it conjures up images of Y2K and computer failures en masse ; but for the wider population, it would have meant very little. Today, it's the phrase that strikes terror into the hearts of even the least tech-savvy individuals. With entire business infrastructures, personal details and financial data now living online, it's not just the NASAs of the world who are at risk.